Cross-linking formation of taro starch (colocasia esculenta)-based hydrogel using freeze-thaw method: synthesis and physical characterization - Luthfianti, Halida Rahmi; Nafisah, Nuraini; Waresindo, William Xaveriano; Sawitri, Asti; Hapidin, Dian Ahmad; Noor, Fatimah Arofiati; Elfahmi, Elfahmi; Edikresnha, Dhewa; Khairurrijal, Khairurrijal (Green and Sustainable Materials Society, 2025)
This study successfully made starch from taro tuber flour using immersion methods (AQ, SM) and centrifugation methods (CE). Taro starch with the AQ method produced the most starch content, thus improving the viscosity parameter in the pasting properties test. A simple mathematical model was used to control the taro starch pasting process and product. The highest R-value in the AQ sample was 309.88 s, indicating the strongest starch granule resistance. Meanwhile, the S-value in this study showed that all samples were above 1, which indicated that water penetration affected the swelling rate of starch granules. Taro starch with different isolation methods was analyzed for hydrogel formation using optical microscopy, SEM, swelling degree test, weight loss, color analysis, and texture profile analysis (TPA). The morphological images show three phases of a taro starch hydrogel formation: granular, potential cross-linking, and cross-linking hydrogel with a firm structure. Optimization of freeze-thaw process parameters was carried out to determine the optimum parameters of starch hydrogel formation, which was obtained under freezing conditions for 17 hours at -23°C and thawing for 7 hours at 4°C. The sample CE resulted in the most stable hydrogel formation, showing the highest amylose content, protein content, and the lowest impurities or ash content. The CE starch concentration of 10% resulted in the highest swelling degree and the lowest weight loss, indicating that the ability of the hydrogel to maintain its structure was stronger and more elastic. The textural properties of CE hydrogel at a concentration of 10% showed the most stability. It had the highest hardness, fracturability, chewiness, and springiness. Physical characteristics showed that the starch hydrogels had a dense, porous surface and formed a cross-linking structure. It can potentially be used in functional food applications to control the release of bioactive compounds.